L'acqua nel paesaggio urbano - Laura, Ferrari (Scuole di dottorato, 2005)
Exploited for requirements of defence, navigation, transport, irrigation, and the powering of mills, water has progressively diminished in importance to the extent that the relations between the city, the territory and the water systems have now greatly deteriorated. This book proposes to retrace the nature of the relations between water and the urban landscape, interpreting the shifting of the relations through images. It also analyses the use of water in contemporary landscape design, identifying the conceptual and compositional tools proper to landscape design which can inform and guide future planning.